2011
DOI: 10.1074/jbc.m111.258780
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal Residues of the Vibrio cholerae Virulence Regulatory Protein ToxT Involved in Dimerization and Modulation by Fatty Acids

Abstract: The regulatory protein ToxT is an AraC family protein that is responsible for activating transcription of the genes encoding cholera toxin and toxin coregulated pilus, which are required for virulence by the human pathogen Vibrio cholerae. The N terminus of ToxT contains dimerization and regulatory elements, whereas the C terminus contains the DNA binding domain. Bile and long chain fatty acids negatively regulate ToxT activity. Utilizing a comprehensive alanine substitution mutant library of ToxT, 19 N-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 40 publications
5
70
2
Order By: Relevance
“…The first two leucines of the AraC, UreR, and XylS triads align with F151 and F152 of Vibrio cholerae ToxT. An F151 alanine substitution results in a monomeric form of ToxT that is unable to bind the tcpA promoter to wild-type levels, resulting in loss of murine intestinal colonization (31). For ExsA, pairwise combinations of the L140A, K141A, and L148A substitutions were sufficient to generate mutants with significant defects in self-association and promoter activation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The first two leucines of the AraC, UreR, and XylS triads align with F151 and F152 of Vibrio cholerae ToxT. An F151 alanine substitution results in a monomeric form of ToxT that is unable to bind the tcpA promoter to wild-type levels, resulting in loss of murine intestinal colonization (31). For ExsA, pairwise combinations of the L140A, K141A, and L148A substitutions were sufficient to generate mutants with significant defects in self-association and promoter activation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…V. cholerae strain KKV2426 (C6706 ΔtoxT::Cm) was created via chitin transformation (27) using genomic DNA from strain SY1002 (28). V. cholerae strains KKV2333 (O395 toxT 5′ UTR U5C), KKV2368 (O395 toxT 5′ UTR U7C), KKV2425 (O395 toxT 5′ UTR U5C, U7C), KKV2382 (C6706 toxT 5′ UTR U5C, U7C), as well as KKV598 (O395 native toxT 5′ UTR) and KKV2372 (C6706 native toxT 5′ UTR), were constructed by using plasmids pKEK1445, pKEK1468, pKEK1469, and pKEK1808 to introduce the mutations into V. cholerae strains KKV2288 (29) and KKV2426 by allelic exchange. A complete list of primers and plasmids used is provided in Tables S1 and S2.…”
Section: Methodsmentioning
confidence: 99%
“…The transcription factor ToxT, belonging to the AraC family, directly activates expression of cholera toxin and toxin-coregulated pilus, but the presence of unsaturated long-chain FFAs inhibits ToxT-dependent activation. Structural and functional analyses of ToxT revealed that unsaturated long-chain FFAs bind directly to a regulatory region in ToxT, suggesting that they prevent ToxT dimerization and/or DNA binding [12][13][14]. Importantly, unsaturated long-chain FFAs have been shown to also inhibit the activity of another member of the AraC family, the HilD virulence regulator in Salmonella enterica [15].…”
Section: How Do Naturally Occurring Free Fatty Acids Sabotage Listerimentioning
confidence: 99%